Population Administration Policy: An Empirical and Juridical Examination - Setiabudhi, Donna Okthalia; Palilingan, Toar Neman; Kermite, Jeany Anita (Brawijaya Law Journal, 2018)
Manado is a city that has a large population, high population mobility and activities in all fields that are increasingly complex. However, actually it does not have a legal product that regulates population administration technically. This paper aims to analyse the population administration policies in the city of Manado and propose an ideal policy that can be pursued to establish an appropriate population administration service in this region. The research is a socio-juridical research. The method used is descriptive by giving a systematic, factual and accurate description of the issues of research.The results indicated that population administration services in the city of Manado were still minimal and not optimal because there were no local regulations which accommodate all the typical conditions of communities. The lack of human resources both in quality and quantity in providing the population administration service to the community and the lack of attention the public to the importance of population administration for their lives, have made inappropriate populatuion administration service. Thus, it is argued that the existence of local regulations are needed to regulate population administration which can accommodate the conditions of the communities in Manado and can be a reference for the implementers in providing optimal services to the community.